A literature review on construction project success evaluation criteria and methods - Goshu Gebremikal Beshah; Wubishet Jekale Mengesha; Belachew Astrey Demiss (Cogent Engineering, 2024)
This literature review emphasizes the importance of stakeholder-responsive success criteria and appropriate evaluation techniques for the construction industry. Traditional evaluation methods can lead to subjective and biased results. Disagreements between industry professionals and researchers on criteria and assessment techniques contribute to ineffective project evaluation. The review aims to identify the most important holistic and stakeholder-responsive success criteria and methods from the literature. The review utilized a systematic approach, downloading 102 references from various databases, including published journal articles, conference proceedings, books, and book sections, using search engines and keywords. The review process involved refining and limiting the number of references using eligibility criteria, with 55 references from 2001 to 2024 being used for review. The review flow chart outlines each step. The findings indicate five main evaluation criteria, such as efficiency, effectiveness, sustainability, environmental impact, and satisfaction. The five evaluation criteria include quality, cost, time, health and safety, environmental impact, stakeholder satisfaction, and lesson learning and development. Furthermore, the quantitative success evaluation method is the best technique due to its reduced subjectivity. The review provides valuable knowledge among industry stakeholders, professionals, academics, and policymakers on the most suitable project success evaluation criteria and methods to evaluate future construction projects.